Today we work with video (II) (Journal of Parents and Teachers, 2014)
We have already filmed a home movie, but now, how to get it edited in a way that is not boring or tedious? This article offers the keys to learning how to import videos, to create interesting transitions, or to add special effects or sounds.
Keywords: video; video editing; keys.